The rs12617336 and rs17574 Dipeptidyl Peptidase-4 Polymorphisms Are Associated With Hypoalphalipoproteinemia and Dipeptidyl Peptidase-4 Serum Levels: A Case-Control Study of the Genetics of Atherosclerotic Disease (GEA) Cohort - Vargas-Alarcón, Gilberto; González-Salazar, María del Carmen; Vázquez-Vázquez, Christian; Hernández-Díaz Couder, Adrián; Sánchez-Muñoz, Fausto; Reyes-Barrera, Juan; Criales-Vera, Sergio A.; Sánchez-Guerra, Marco; Osorio-Yáñez, Citlalli; Posadas-Sánchez, Rosalinda (Frontiers in Genetics, 2021)
Dipeptidyl peptidase-4 (DPP4) can influence lipid homeostasis and atherosclerosis progression. We aimed to assess the association of DPP4 gene polymorphisms with hypoalphalipoproteinemia and DPP4 serum levels, in a cohort of Mexican individuals. Five DPP4 polymorphisms (rs12617336, rs12617656, rs1558957, rs3788979, rs17574) were genotyped in 748 participants with and 745 without hypoalphalipoproteinemia. The associations were evaluated using logistic regression analyses. Under inheritance models adjusted for confounding variables, the rs12617336 (OR = 0.22, Pheterozygote = 0.001) and rs17574 (OR = 0.78, Padditive = 0.022; OR = 0.73, Pdominant = 0.012; OR = 0.73, Pheterozygote = 0.017; OR = 0.72, Pcodominant1 = 0.014) minor alleles were associated with a low risk of hypoalphalipoproteinemia. After the correction for multiple comparisons, the associations were marginal except the association of the rs12617336 that remaining significant. Additionally, both DPP4 minor alleles were associated with protection for the presence of insulin resistance (IR) (OR = 0.17, Pheterozygote = 0.019 for rs12617336 and OR = 0.75, Padditive = 0.049 for rs17574). The rs12617336 minor allele was also associated with a low risk of hyperinsulinemia (OR = 0.11, Pheterozygote = 0.006). Differences in DPP4 levels were observed in individuals with rs17574 genotypes, the rs17574 GG genotype individuals had the lowest levels. Our data suggest that rs12617336 and rs17574 DPP4 minor alleles could be envisaged as protective genetic markers for hypoalphalipoproteinemia, IR, and hyperinsulinemia. The rs17574 GG genotype was associated with the lowest DPP4 levels.